MANAJEMEN KELEMBAGAAN DAN AKADEMIK LEMBAGA PENDIDIKAN MA’ARIF NAHDLATUL ULAMA KOTA SAMARINDA KALIMANTAN TIMUR - Abdurrahman AR; Susilo Susilo; Labulan Labulan (PENDAS MAHAKAM: Jurnal Pendidikan dan Pembelajaran Sekolah Dasar, 2017)
The objective of this research was to identificate the  Educational management and Academic quality and to doctrine the religious values to the basic  Ma’arif Nahdlatul UlamaInstitute in Samarinda city East Kalimantan. This research also designed to get the object datas from the three Islamic Elementry schools which organized by Ma’arif Nahdlatul Ulama Samarinda city through many kinds ways they are : (1)Interviews The Chief of LP. Ma’arif NU, interview to three Elementry head master and other sources who bonafide informan,(2) take pictures,(3) take  school’s datas or documents. The information from data collected people knewn that the Moslem Elementry School  Ma’arif Nahdlatul Ulama conditions in the some ares in Samarinda city  has weakness and and lackness their Institution manajement and academic manajement, because the school there hasn’t any long term program, middle term program and short term program showed to researcher as their documents. The result of datas analysis these indicate three of Moslem Elementry School  Ma’arif NU those located in Samarinda city, they are MI 01 in Palaran, MI.02 Sindang Sari, MI 03  Jln. Rukun Samarinda Seberang, they were still runing slowly. The researcher’s summary in this research that, from the three of Ma’arif NU Samarinda, they’re still need high skills to construct these institutions